Free boundary problems theory and applications - Colli Pierluigi; Verdi Claudio; Visintin Augusto (Basel Birkhauser Verlag, 2004)
Many phenomena of interest for applications are represented by differential equations which are defined in a domain whose boundary is a priori unknown, and is accordingly named a free boundary. A further quantitative condition is then provided in ord
Keywords: Boundary value problems